Correction: Countermovement push-up test to assess the upper extremity force-time characteristics in swimmers during a macrocycle. - Ferhat Öztürk; Evrim Ünver; Aykut Özçadırcı; Şükrü Alpan Cinemre; Gizem İrem Kınıklı (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0289573.].